Performance optimization of combined cycle power plant considering various operating parameters / Sachin Kumar - Kumar, Sachin (Universiti Teknologi MARA, 2021)
Combined cycle power plants are popular in thermal engineering field for their higher efficiency as compared to normal cycles such as Rankine and Brayton Cycle. But main disadvantages of the cycle are waste heat rejection and low work output. To overcome these difficulties a heat recovery system is used in present work to recover waste heat of Brayton cycle as a steam generator for Rankine cycle in a combined Gas-Vapor cycle. In present work, effect of factors such as “compression ratio”, “inlet air temperature” and “turbine inlet temperature” on cycle efficiency was calculated. It was found that cycle efficiency increases with increase in these factors. It was found that optimum value of compression ratio is 12-18 for maximum output of combined cycle. Whereas inlet air temperature has adverse effect on cycle efficiency so it should be kept lower while increase in turbine inlet temperature increases the cycle’s work output and hence efficiency. Optimum values of turbine inlet temperature were found in range of 1600-1700 K